Assessing the safety and efficacy of drugs used in preparing the nose for diagnostic and therapeutic procedures: a systematic review. (11th February 2016) - Saif, A.M.; Farboud, A.; Delfosse, E.; Pope, L.; Adke, M.
Abstract : Background: Local anaesthetics and vasoconstrictors are essential for pain control and to aid intra‐operative haemostasis in nasal procedures. They also improve access, and reduce discomfort when performing nasal endoscopy. There are no clear guidelines on preparing the nose despite evermore diagnostic and therapeutic procedures utilising the nose as a point of access. Objective of review: This review aims to identify nasal preparations used in diagnostic and therapeutic nasal procedures and to examine their safety and efficacy. Type of review: Systematic review. Search strategy: A search was carried out using PubMed, MEDLINE, Ovid EMBASE, the Cochrane library and references from the included articles. Evaluation method: The inclusion criteria included: full‐text English language articles with regard to nasal preparation for surgery. Case reports, systematic reviews, meta‐analysis, double‐blind placebo controlled randomised trials (RCTs) and case series were included. Results: A total of 53 articles were retrieved: 13 articles on nasal preparation for operative procedures, six on functional endoscopic sinus surgery and 22 on nasendoscopy as well as six case reports. Cocaine was the most widely used topical preparation for operative procedures but was associated with more side‐effects; thus, topical tetracaine and levobupivacaine infiltration are alternatives with equivalent efficacy but reduced adverse effects. All articles reviewed for functional endoscopic sinus surgery used a mixture containing lidocaine, adrenaline or both. Flexible nasendoscopy causes minimal patient discomfort and preparation is only recommended in selected patients, in contrast to rigid nasendoscopy which requires preparation. Conclusion: For operative procedures, such as septorhinoplasty, a single agent tetracaine or levobupivicaine provides an improved surgical field. In functional endoscopic sinus surgery, lidocaine–adrenaline preparations have resulted in significantly better surgical and patient outcomes. There is little evidence to support the routine use of pre‐procedural nasal preparation for flexible nasendoscopy. Those undergoing rigid endoscopy conversely always require the use of a vasoconstrictor and local anaesthetic. Pre‐procedure assessment of patients is recommended, with agents being reserved for those with low pain thresholds, high anxiety and small nasal apertures presenting resistance to the insertion of the endoscope.